Digital Green Economy: Integration Of Financial Technology And Circular Economy As A Sustainable Transition Strategy In Developing Countries - Pasha, Elsa Islammia (GEMA EKONOMI, 2025)
Global economic transformation demands that developing countries shift to a more sustainable development model amidst the climate crisis, inequality, and technological disruption. This study aims to analyze the integration of financial technology (fintech) and the circular economy in building a digital green economy as a sustainable transition strategy. Using a qualitative approach based on a conceptual literature review, data was collected through a systematic review of academic articles, international reports, and public policies. The analysis shows that fintech plays a crucial role in providing inclusive financing, strengthening transparency through blockchain, and encouraging innovation in green financial products. On the other hand, the circular economy offers a low-carbon production and consumption paradigm through the principles of reduce, reuse, and recycle. The integration of the two creates strategic synergy in expanding green financial inclusion, increasing resource efficiency, and mitigating the risk of resistance to environmental transitions. However, challenges such as the digital divide, low financial literacy, and weak regulations still need to be addressed. This study recommends a multi-level strategy involving governments, the private sector, academia, and communities to accelerate the adoption of the digital green economy in developing countries.